Synthesis and Characterization of New Sandwiched and multi Decker Palladium Organometallic Compounds of alkylated S-Indacene (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
A synthesis of mono nuclear bis indacene mono  metal compound of type [L-M-L] where (L is 2,6- diethyl-4,8-dimethyl-1,5-dihydro-s-indacene, M=Pd. Pd-bis (ƞ5-2,6-diethyl-4,8-dimethyl-1,5- dihydro-s-indaceneide) [Pd (Ic’H)2], and the  oligomeric form of this compound is successfully  prepared. The prepared compound is of the type  [L-M-L-M-L-M-L] where M= Pd and L =-2,6- diethyl-4,8-dimethyl-1,5-dihydro-s-indaceneide)}]  [Ic’Pd(µ-Ic’) Pd (µ-Ic’)PdIc’] the reaction yields a  almost quantitative yield. The synthesized  compounds were characterized by NMR (1H and 13C), and elemental analysis. The spectroscopic  data reveals the formation Multidecker  compound. This oligomer is further subjected to  catalytic property study
Keywords: palladium organometallics; s indacene; multidecker; sandwich